DEVELOPMENT OF EDUCATION GAME "HALO INDONESIA" BASED ON ANDROID FOR WALAILAK UNIVERSITY STUDENTS OF THAILAND - Wanda Ramansyah; Ariesta Kartika Sari; Pensri Panich; Nurrohmat Hidayatullah Akbar (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
The obstacle experienced by Thai citizens to learn Indonesian is the difficulty ofpronouncing the letters and words in Indonesian properly and correctly. To overcomethese obstacles, a solution is needed in the form of developing an educational game"Halo Indonesia" for learning Indonesian for Thai citizens. This educational game willprovide clear instructions on how to pronounce letters and words in Indonesianbecause there are sounds and writing to guide users to learn.